Identifikasi Serovar Penyebab Leptospirosis pada Anjing di Yogyakarta - Guntari Titik Mulyani; Sri Hartati; Hastari Wuryastuty; Ida Tjahajati; Yuriadi Yuriadi; Irkham Widiyono; Yanuartono Yanuartono; Hary Purnamaningsih; Soedarmanto Indarjulianto; Slamet Raharjo; Alfariza Nururozi; Angeline Ganapragasam; Yeo Suan Jiao (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
Leptospirosis is a zoonotic disease of global concern, and is caused by pathogenic serovar Leptospira interrogans. Canine Leptospirososis is widespread worldwide, dogs can act as incidental hosts or maintenance hosts for various serovars. The purpose of this research was to identify leptospire serovars that infect healthy and suspected leptospirosis dogs in Yogyakarta. A total of 56 dogs (36 healthy dogs and 20 suspect leptospirosis dogs) sera were taken from cephalica vein as much as 3 ml. Sera were examined for leptospirosis with Microscopic Aglutination Test (MAT) which conducted at the Research Center for Veterinary Science, Bogor. Microscopic Aglutination Test carried out on various Leptospire serovar, namely: Ichterohaemorrhagiae, Javanica, Celledoni, Ballum, Pyogenes, Cynopeteri, Rachmati, Australis, Pomona, Canicola, Grippotyphosa, Bataviae, Hardjo, and Tarrasovi. The results showed that Celledoni serovars infected 25% of healthy dogs and 5% of suspect leptospirosis dogs, Javanica serovar infected 19% of healthy dogs, Bataviae serovars infected 15% of suspect leptospirosis dogs, Grippotyphosa serovar infected 11% of healthy dogs, Tarrasovi serovar infected 10% of suspect leptospirosis dogs, serovars Cynopteri infects 5% of healthy dogs and 5% of suspect leptospirosis dogs, serovar Pyrogenes infects 5% of healthy dogs and 5% of suspect leptospirosis dogs, and serovar Rachmati infects 5% of suspect leptospirosis dogs. Seven healthy dogs (19%) and 2 suspect leptospirosis dogs (10%) were infected with more than 2 leptospire serovars. From the results of this study it can be concluded that Celledoni serovar of Leptospira interrogans infection causes subclinical leptospirosis, while Bataviae serovar infection causes clinical leptospirosis in dogs in Yogyakarta.